What are Internal medicine residents' attitudes toward obesity as a disease, people living with obesity, and obesity treatment? - Kacey Chae; Jashalynn German; Karla Kendrick; Sean Tackett; Paul O'Rourke; Kimberly A. Gudzune; Marci Laudenslager (Wiley, 2024)
Abstract Objective Despite the rising prevalence of people living with obesity, physicians are providing suboptimal care to these individuals, which may be a consequence of inadequate education in weight management and negative attitudes toward people living with obesity. Internal Medicine (IM) residency is an ideal setting to address physicians' attitudes toward people living with obesity. However, there is a paucity of recent literature on this topic. This study sought to assess the current attitudes of IM residents toward obesity as a disease, people living with obesity, and obesity treatment. Methods A cross‐sectional survey was conducted in 2020 across two IM programs assessing residents' attitudes toward obesity as a disease, people living with obesity, and obesity treatment. RESULTS Among 42 residents who participated in the survey, 64% were women; 31 percent were Post Graduate Year 1, 31% PGY‐2, and 38% PGY‐3. Mean attitude scores were high on statements regarding obesity as a chronic disease [4.7 (SD 0.4)] and its association with serious medical conditions [4.9 (SD 0.3)]. Residents had overall positive attitudes toward people living with obesity. In contrast, residents felt negatively regarding their level of success in helping patients lose weight [2.0 (SD 0.7)]. CONCLUSIONS While residents recognized obesity as a chronic disease and had positive attitudes toward people living with obesity, their low ratings regarding weight management success suggest that targeted educational efforts are needed to increase obesity treatment self‐efficacy.